Multifunctional Coding Metasurface With Left and Right Circularly Polarized and Multiple Beams - Li, Sijia; Li, Zhuoyue; Han, Bowen; Huang, Guoshuai; Liu, Xiaobin; Yang, Huanhuan; Cao, Xiangyu (Frontiers in Materials, 2022)
In this paper, a multifunctional coding metasurface (MCMS) has been proposed to realize dual-circularly polarized beams and beam focusing with transmission and reflection. The phase of transmissive wave is controlled by rotating the elements, and the corresponding element, which consists of two quadrate voids etched on a single layer substrate, is designed for the metasurface with Pancharatnam-Berry (PB) phase. The phase distribution of the circularly polarized four-beam is determined according to the convolution theorem of patterns and the phase compensation principle. In order to validate the proposed metasurface, the multifunctional meta-device is fabricated and measured to illustrate the four-beam with left circular polarization in transmissive space and the right circularly polarized four-beam in reflective space by MCMS with x-polarized incidence. The experimental results heavily agree with the simulated data. The MCMS has potential applications in wireless communications due to its low profile, compact, and lightweight features.